The geography of learning: Ferrari Gestione Sportiva 1929-2008 - Jenkins, Mark; Tallman, Stephen (Oxford University Press, 2015)
This article considers the mechanisms that permit and enhance the movement of highly tacit component (technical) knowledge and geographically sticky architectural knowledge across borders and between clusters and firms. We address a number of critical research questions that relate to intra- and inter-locational knowledge transfer. We use a theory-driven, longitudinal, single case study to develop a conceptual framework to examine and describe how shifting the geography of knowledge sourcing can facilitate architectural change by following the transformation of one business unit within a specialist global organization through a series of evolutionary steps that involved internalizing new component knowledge from other firms and locations, transforming the company’s architectural knowledge through various transactions with firms and individuals from a foreign cluster, and eventually radically transforming the concept of the firm and its focus. We close by generalizing this model to address the fundamental processes of the spatial aspects of organizational learning.